KEJADIAN RUPTUR PERINEUM DITINJAU DARI UMUR DAN PARITAS IBU - Willy Astriana (Masker Medika, 2023)
ABSTRACT Introduction: Efforts to prevent perineal rupture are to protect the perineum in the second stage of labor when the baby's head opens the vulva (5-6 cm in diameter). according to the Minister of Health regulation number 28 of 2017 concerning licensing and implementation of midwife practice, midwives provide high quality care, care for mothers, respond to local culture during childbirth, lead clean and safe deliveries, handle certain situations and emergencies to optimize the health of women and their newborns. The purpose of this study was to determine the relationship between age and parity of mothers with the incidence of perineal rupture in the Working Area of Puskesmas Bangsa Negara, Belitang District, East Ogan Komering Ulu Regency in 2022. Method: This study used an analytic method with a Cross Sectional approach. The population was all mothers giving birth. The sampling technique used was the total population of 75 respondents. Data analysis used univariate analysis and bivariate analysis using distribution tables and Chi-Square statistical tests, with a 95% confidence level. Result: Research results on univariate analysis of 75 respondents who experienced perineal rupture as many as 54 respondents (63.53%) and who did not as many as 31 respondents (36.47%). Of the 75 respondents aged <20 and > 35 as many as 66 respondents (77.65%) and aged 20-30 as many as 19 respondents (22.35%). And of the 85 respondents, nulliparous parity was 0 respondents, primiparous was 64 respondents (75.29%), multiparous was 21 respondents (24.71%), grandemultiparous was 0 respondents and great grandemultiparous was 0 respondents. In bivariate analysis, the p value is 0.036 for age and parity p value is 0.021. In conclusion: there is a relationship between age and parity with the incidence of perineal rupture.